The effects of French contrast training on lower limb athletic performance in healthy adults: a systematic review and meta-analysis - Zhao, Ziren; Ma, Zhili; Wu, Chao; Zheng, Xin; Liu, Tingyuan; Deng, Nijiao; Zhou, Kaixiang (Frontiers in Physiology, 2025)
BackgroundFrench Contrast Training (FCT) is a unique complex training (CT) method that has gained attention in sports science. Participant characteristics, training protocols, and control group types may influence the effects of FCT on lower limb athletic performance.ObjectiveThe aim of this systematic review and meta-analysis was to assess the effects of FCT on jump, sprint, and maximal strength in healthy adults and to identify potential moderators of training effects.MethodsWe searched five databases (PubMed, Web of Science, Embase, EBSCO, and CNKI). Seven randomized controlled trials with 195 participants were included. We used a random-effects model for the outcomes (jump, sprint, and maximal strength) to calculate the pooled effect sizes (standardized mean differences, SMD). Subgroup analyses and GRADE assessments were conducted to explore heterogeneity and assess the quality of evidence.ResultsFCT significantly improved sprint (large effect: SMD = −0.92; 95% CI: 1.30 to −0.55; p < 0.001) and jump performance (moderate effect: SMD = 0.62; 95% CI: 0.33 to 0.91; p < 0.001). However, FCT failed to significantly improve maximal strength (small effect: SMD = 0.43; 95% CI: 0.04 to 0.89; p = 0.07). Subgroup analyses revealed that control group type, training frequency, training load, and participant characteristics were moderating variables influencing training effects.ConclusionFrench contrast training is more effective than traditional resistance training for enhancing lower limbs explosive performance in healthy adults. However, there is not enough evidence to show it is superior to traditional complex training or that it improves maximal strength. Future research should aim to optimize FCT protocols and explore long-term adaptability across different populations.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php, identifier CRD420251000409.